Toxoplasma gondii Myocarditis after Adult Heart Transplantation: Successful Prophylaxis with Pyrimethamine. (1st November 2012) - Strabelli, Tania Mara V.; Siciliano, Rinaldo Focaccia; Vidal Campos, Silvia; Bianchi Castelli, Jussara; Bacal, Fernando; Bocchi, Edimar A.; Uip, David E.
Abstract : Toxoplasma gondii primary infection/reactivation after solid organ transplantation is a serious complication, due to the high mortality rate following disseminated disease. We performed a retrospective study of all cases of T. gondii infections in 436 adult patients who had received an orthotopic cardiac transplant at our Institution from May 1968 to January 2011. Six patients (1.3%) developed T. gondii infection/reactivation in the post-operative period. All infections/reactivations occurred before 1996, when no standardized toxoplasmosis prophylactic regimen or co-trimoxazole prophylaxis was used. Starting with the 112th heart transplant, oral pyrimethamine 75 mg/day was used for seronegative transplant recipients whose donors were seropositive or unknown. Two patients (33.3%) presented with disseminated toxoplasmosis infection, and all patients (100%) had myocarditis. Five patients (83.3%) were seronegative before transplant and one patient did not have pre-transplant serology available. Median time for infection onset was 131 days following transplantation. Three patients (50%) died due to toxoplasmosis infection. After 1996, we did not observe any additional cases of T. gondii infection/reactivation. In conclusion, toxoplasmosis in heart allographs was more frequent among seronegative heart recipients, and oral pyrimethamine was highly effective for the prevention of T. gondii infection in this population.